2020
DOI: 10.3389/fpsyt.2020.551315
|View full text |Cite
|
Sign up to set email alerts
|

Relations of COVID-19-Related Stressors and Social Support With Chinese College Students' Psychological Response During the COVID-19 Pandemic

Abstract: This study examines the main and interactive relations of stressors and social support with Chinese college students' psychological symptoms (e.g., anxiety, depression) during the COVID-19 pandemic. All the constructs are assessed by self-report in an anonymous survey during the pandemic outbreak. The results show that the number of stressors has a positive relation with psychological symptoms, and social support has a negative relation with psychological symptoms. In addition, social support serves as a buffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
69
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(90 citation statements)
references
References 44 publications
18
69
1
2
Order By: Relevance
“…The COVID-19-related stressors checklist ( 18 ) was used to assess the participants' experience of COVID-19-related stressors. The checklist consisted of 16 COVID-19-related stressors that were generalized into the following six groups: self-related events, family-related events, friend-related events, acquaintance-related events, information-related events, and other infectious disease-related events.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The COVID-19-related stressors checklist ( 18 ) was used to assess the participants' experience of COVID-19-related stressors. The checklist consisted of 16 COVID-19-related stressors that were generalized into the following six groups: self-related events, family-related events, friend-related events, acquaintance-related events, information-related events, and other infectious disease-related events.…”
Section: Methodsmentioning
confidence: 99%
“…Previous research showed that some demographic variables (e.g., gender, social-economic status) can predict individual adjustment during the pandemic ( 18 ). Therefore, both variables of gender and socioeconomic status were used as control variables in present study.…”
Section: Methodsmentioning
confidence: 99%
“…These findings suggest that it is less probable that students seek help from friends and family when they feel angry, frustrated, bored, or alone, but they may seek help if experiencing fear or confusion during the lockdown. In this regard, the results of Li et al ( 2020 ) confirmed that social support has a significant negative predictive effect on anxiety, which is also present during pandemics. Finally, turning to religion as a strategy to cope with lockdown was positively related to hope, joy, gratitude, compassion, and fear.…”
Section: Discussionmentioning
confidence: 85%
“…COVID-19-related stressors. The COVID-19-related stressors scale [14] was used to assess the stressors related to infectious disease. The scale includes 16 items, and one of items is listed as "One of your close friends was diagnosed with COVID-19".…”
Section: Measurementmentioning
confidence: 99%